Visions of Justice Sharīʿa and Cultural Change in Russian Central Asia - Sartori, Paolo (Handbook of Oriental Studies. Section 8 Uralic & Central Asian Studies, 2016)
In Visions of Justice Paolo Sartori surveys the role of Russian colonialism in affecting the way in which Muslims in Central Asia formulated their convictions about right and wrong and became exposed to different notions of morality. Readership: All interested in the history of post-Mongol Central Asia, in the social dynamics of the wider Islamic world, as well as (Islamic) legal history.